2020
DOI: 10.1080/00393630.2020.1857523
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Archaeological High-tin Bronze Corrosion Structures

Abstract: Since ancient times the use of high-tin bronze alloys (>17 wt.%) has been mainly limited to the production of specific objects such as mirrors and bells. High-tin bronzes can show distinctive colour reflection, as well as mechanical properties and corrosion resistance that clearly distinguish it from the classical bronze composition (with 8-12 wt.% Sn). In the present study samples of archaeological high-tin bronze bells were studied by optical microscopy, SEM-EDS and Raman imaging with the aim of characterisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The lead-rich globules could be formed during solidification of the cast: lead was segregated due to its limited solubility in copper and solidified forming the grains revealed by SEM-EDS. 28,31,32 The investigated part of A2 surface appears more homogeneous but also here little spots of higher lead density are recognized. Simultaneous Si and O high concentrations in some parts of the surface can be directly attributed to silica or silicates incorporated into the arrowhead's external layer (see Supporting Information).…”
Section: Elemental Analysismentioning
confidence: 83%
See 1 more Smart Citation
“…The lead-rich globules could be formed during solidification of the cast: lead was segregated due to its limited solubility in copper and solidified forming the grains revealed by SEM-EDS. 28,31,32 The investigated part of A2 surface appears more homogeneous but also here little spots of higher lead density are recognized. Simultaneous Si and O high concentrations in some parts of the surface can be directly attributed to silica or silicates incorporated into the arrowhead's external layer (see Supporting Information).…”
Section: Elemental Analysismentioning
confidence: 83%
“…The grainy structure is also clearly seen in the electron image. The lead‐rich globules could be formed during solidification of the cast: lead was segregated due to its limited solubility in copper and solidified forming the grains revealed by SEM‐EDS 28,31,32 …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of the atmospheric alteration of bell bronze had shown a microinfiltrative property of the patina and the development of preferential α/δ corrosion of the underlying alloy [ 10 , 11 ]. They were performed on samples corroded over a long term.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most famous bell bronzes, one can mention Big Ben in the United Kingdom (1858), the bell of the Yongle regime in Pekin (1420) but also the bells of “Notre Dame de Paris” in France whose replacement in 2013 was widely publicized. The corrosion of bell bronzes has been poorly studied, with the exception of [ 10 , 11 ] that show that the long-term corrosion of the bell is governed by micro-infiltrating net-works of environmental fluids through brittle corrosion products that lead to a different α/δ corrosion behavior: a multilayer corrosion of the α-phase, while the corroded δ-phase is enriched in tin oxide. However, a question arises: can the atmospheric alteration also change the bronze vibration modes?…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000, the largest and heaviest ringing bell in the world has been the Bell of Good Luck at the Foquan Temple in Pingdingshan city, China, whose mass is 116 × 10 3 kg [126,127]. The shape of bells has changed over the centuries [128][129][130]; nevertheless, their construction was designed to have suitable strength and divine sound using properly selected parameters, i.e., wall thickness, bell diameter, and the composition of the alloy, which are decisive concerning the sound tone and timbre [131][132][133]. The optimal mechanical strength is easy to achieve by increasing the bell wall thickness, but the relationship between the shape of the bell and its sound is hard to grasp, especially because the bell sound consists of a series of merged tones and overtones, which give the so-called strike tone [134,135].…”
Section: Lwc For Bellsmentioning
confidence: 99%